DETERMINATION OF QUALITATIVE INDICATORS OF MILK FOR FOOD SAFETY (Web of Technology: Multidimensional Research Journal, 2024)
The article presents the results of studies on the problem of the content of somatic cells in cow's milk. It is shown that with an increase in the number of somatic cells, the composition of milk and its physicochemical properties change. These changes, in turn, lead to a deterioration in its technological properties, a decrease in the quality characteristics of milk and finished products. The quality of milk depends on many factors and is determined by many indicators separately identified in the standard. One of the main and important indicators is the number of somatic cells - cells of various tissues and organs. The number of somatic cells depends on a number of factors, such as the age of the cow, breed, physiological state of the animal, periods of lactation, breast diseases of various etiologies. Inside the udder there is a constant renewal of epithelial tissue cells, old cells die and are rejected. Milk, even from a healthy cow, always contains somatic cells that have been shed from the secretor part of the udder. In particular, these are cells of cylindrical, squamous and cubic epithelium of the mammary gland, leukocytes, erythrocytes.